Analisis Difusi Inovasi pada Inovasi Produk Batik di Kelurahan Jenggot Dalam Mendukung Upaya Pengembangan Ekonomi Lokal Kota Pekalongan - Aulia Rachmi Isra; Mohammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2022)
The development of innovation in a particular area cannot be separated from the diffusion of innovation. This diffusion of innovation occurs because of the process of social interaction by related actors in the region. This is explained by Rogers (2003), that the diffusion of innovation is a process when innovation is communicated or mentioned through certain channels for a certain period of time to members of a social system, which then becomes part of the social system. With the diffusion of innovation, an area will experience changes in certain conditions due to the impact of emerging innovations, which will play a role in developing the character of the region. As happened in Jenggot village, the emergence or entry of new patterns influenced changes in the market in terms and the direction of development of the existing batik patterns in the village. Batik patterns that were originally patterned and impressed monotonously with plant and animal-based patterns are becoming more contemporary and fashionable. The diffusion of innovation helps business owners either directly or indirectly in promoting their batik products. Thus increasing the value of the batik product itself.